HUBUNGAN INTENSITAS MEDAN DEKAT DENGAN DELTA PROFIL INDEKS BIAS (ï(X,Y)) PADA GRADE INDEKS FIBER OPTIK - Meiliayana, Meiliayana (Jurnal Teknik Elektro, 2002)
Fiber optic refractive index profile can be reconstructed from its mode field distribution. Toanalyzed this mode field image (digital image form), one formula, which derived from scalarwave equation, is needed to describe a relationship between the intensity and refractiveindex value as a radial function. This paper included numerical analysis to solve the secondorder differentiation and made the formula more suitable for computer process.Keywords: mode field distribution, scalar wave equation, refractive index, numericalanalysis